The real motives behind the emergence of the Anglican Church 1509-1547 - ربيع الموسوي (آداب الكوفة, 2010)
It is noteworthy to say that the dispute and conflict between the royal institution and the institution and the church is very old, extending back to the era of their emergence as two institutions together, and perhaps what led to fueling the dispute between the two parties, especially after the discovery of the falsity and forgery (the gift of Constantine). In the late Middle Ages, the papal institution began to go through dark stages, and it reached a dangerous stage of deterioration and decline. a Historians consider the conversion of the English to Christianity as one of the important events in both English and European history.